The onset process of the 2018/2019 Indonesian–Australian summer monsoon: The importance of the air–sea interaction - Duan, Yongliang; Liu, Hongwei; Feng, Ming; Song, Xiangzhou; Li, Kuiping; Liu, Lin; Liu, Baochao; Yang, Guang; Yu, Weidong (Frontiers in Marine Science, 2023)
The Madden–Julian oscillation (MJO) and its associated air–sea interactions during the onset process of the 2018/2019 Indonesian–Australian summer monsoon (IASM) are investigated based on the in situ data from a moored buoy off the coast of northwest Australia, along with ERA5 reanalysis and satellite data. The results verify that the IASM onset in mid-December 2018 was triggered by the first-branch eastward-propagating MJO (FEMJO) originating from the tropical Indian Ocean. However, the strong negative SST anomaly (SSTA) was evident off northwest Australia, which weakens FEMJO over northern Australia and shifts the convective center further northward. The mixed layer heat budget analysis based on the buoy observations reveals that the increased latent heat loss that occurred before the arrival of the FEMJO convection was primarily attributed to the large air–sea temperature difference and strong winds, resulting in the pronounced SSTA.